A vertical-oriented WS2 nanosheet sensitized by graphene: an advanced electrocatalyst for hydrogen evolution reaction. Issue 35 (19th August 2015) - Shifa, Tofik Ahmed; Wang, Fengmei; Cheng, Zhongzhou; Zhan, Xueying; Wang, Zhenxing; Liu, Kaili; Safdar, Muhammad; Sun, Lianfeng; He, Jun
Abstract : We report the successful synthesis of vertical-oriented ultrathin rGO decorated WS2 nanosheets. This novel material demonstrates superior performance in hydrogen evolution. Abstract : Electrocatalytic hydrogen production at low overpotential is a promising route towards a clean and sustainable energy. Layered transition metal dichalcogenides (LTMDs) have attracted copious attention for their outstanding activities in hydrogen evolution reaction (HER). However, the horizontally laid nanosheets suffer from a paucity of active edge sites. Herein, we report the successful synthesis of vertical-oriented WS2 nanosheets through a hydrothermal method followed by a facile sulfurization process. Furthermore, the surface of synthesized WS2 nanosheets was decorated by ultrathin reduced graphene oxide (rGO) nanoplates. This is achieved for the first time by bringing the rGO on the surface of vertical-oriented WS2 nanosheets, which is conducive to rapid electron transport during the HER process. Significantly, the as-synthesized rGO/WS2 nanosheets exhibit improved HER activity as compared to the undecorated ones. It needs a low overpotential of only 229 mV vs. RHE to afford a current density of 10 mA cm −2 . We believe that this hybrid structure demonstrated remarkable HER activity brought about by a compatible synergism between rGO and WS2 .